The Effect of Health Education on Diet Compliance Among Patients with Diabetes Mellitus in the Sukaraja Public Health Center’s Work Area in Sukabumi Regency - Dewi, Rosliana; Nida Rahayu; Waqid Sanjaya; Dila Nurul Arsyi; Johan Budhiana (STIKep PPNI Jawa Barat, 2022)
Aims: There is a significant public health problem in which the number of people diagnosed with diabetes is increasing year after year. One possible explanation for this is a lack of adherence to the DM diet. As a result, it is critical to conduct health education regarding DM diet compliance. The purpose of this study was to assess the effect of health education on dietary compliance in patients with diabetes mellitus in the Sukaraja Public Health Center's work area in Sukabumi Regency. Methods: This study employs a quasi-experimental design with a non-equivalent control group. Purposive sampling was used to collect the sample. 38 respondents were divided into two groups, each with 18 respondents: the intervention group and the control group. Analysis of data using the Paired Sample T-Test and the Independent Sample T-Test. Results: After health education in the intervention group, there was an increase in dietary compliance in patients with diabetes mellitus (p = 0.004), and in the control group there was an increase in dietary compliance (p = 0.021) and there was a difference between dietary adherence in the intervention group and the control group (p = 0.024). Conclusion and Suggestion: There is an influence of health education on the dietary compliance of diabetes mellitus patients, so it is hoped that this health education can be provided continuously to improve the dietary compliance of diabetes mellitus patients and serve as an evidence-based practice for the Sukaraja Health Center.